A novel heterozygous mutation of the WFS1 gene leading to constitutive endoplasmic reticulum stress is the cause of Wolfram syndrome. Issue 8 (8th March 2017) - Morikawa, Shuntaro; Tajima, Toshihiro; Nakamura, Akie; Ishizu, Katsura; Ariga, Tadashi
Abstract : Background: Wolfram syndrome (WS) is a disorder characterized by the association of insulin‐dependent diabetes mellitus (DM), diabetes insipidus, deafness, and optic nerve atrophy. WS is caused by WFS1 mutations encoding WFS1 protein expressed in endoplasmic reticulum (ER). During ER protein synthesis, misfolded and unfolded proteins accumulate, known as "ER stress". This is attenuated by the unfolded protein response (UPR), which recovers and maintains ER functions. Because WFS1 is a UPR component, mutant WFS1 might cause unresolvable ER stress conditions and cell apoptosis, the major causes underlying WS symptoms. We encountered an 11‐month‐old Japanese female WS patient with insulin‐dependent DM, congenital cataract and severe bilateral hearing loss. Objective: Analyze the WFS1 and functional consequence of the patient WFS1 in vitro. Results: The patient WFS1 contained a heterozygous 4 amino acid in‐frame deletion (p.N325_I328del). Her mutant WFS1 increased GRP78 and ATF6α promoter activities in the absence of thapsigargin, indicating constitutive ER stress and nuclear factor of activated T‐cell reporter activity, reflecting elevated cytosolic Ca 2+ signals. Mutant transfection into cells reduced mRNA expression levels of sarcoplasmic/endoplasmic reticulum Ca 2+ transport ATPase 2b (SERCA2b) compared with wild type. Because SERCA2b is required for ER and cytoplasmic Ca 2+ homeostasis, decreased SERCA2b expression might affect ER Ca 2+ efflux, causing cell apoptosis. Conclusion: A novel heterozygous mutation of WFS1 induced constitutive ER stress through ATF6α activation and ER Ca 2+ efflux, resulting in cell apoptosis. These results provide new insights into the roles of WFS1 in UPR and mechanism of monogenic DM.